Socioeconomic and Environmental Impact of Development Interventions: Rice Production at the Gallito Ciego Reservoir in Peru - Chavez, H.; Nadolnyak, D; Saravia, Miguel (2013)
Apart from direct economic impacts, development projects have complex social and environmental impacts among which sustainability plays a major role. The Gallito Ciego reservoir was built to increase and improve agricultural production at the Jequetepeque valley in Peru. Cost-benefit analysis of rice production from 1992 to 2007 is used to measure the immediate economic impact of the project. Also, a matrix of other relevant impact indicators is constructed to expose changes in the project’s environment during its life cycle. The main conclusion is that, even though there is a significant positive increase in income from agricultural production, the social and environmental impacts are not necessarily positive.